偏鄉國中全英語教學對國中學生英語口說能力之影響 Implementing English-only Instruction to Promote the English Speaking Proficiency of Rural Junior High School Students - 李妙慈 Miao-Tzu Lee; 鍾鳳嬌 Feng-Chiao Chung; 王國川 Kuo-Chang Wang (National Changhua University of Education, 2021)
本研究旨在探究國中英語科全英語教學對學生口說能力之影響，採質量並重的行動研究法，以屏東縣樂樂高中(化名)國中部二年級學生為研究對象，進行每週兩堂課，為期十週的全英語教學活動。教材為康軒版國民中學第三冊英語課本及「大家說英語」2018年9月份雜誌內容，並據此發展十週全英語教學課程方案。藉由授課之外籍教師及協同教學者自編測驗，評量23位學生的英語口說能力表現。本研究透過課堂觀察、結構式訪談、學生回饋單等方式進行資料蒐集、整理、分析與歸納，以進一步了解全英語教學對學生英語口說能力之影響。研究結果發現全英語教學需搭配符合學生需求的全英語教學課程方案以達教學目的；全英語教學課程方案之實施歷程對溝通互動的設計需求高，其次，全英語教學課程方案之實施歷程需要差異化課程設計；全英語教學課程對國中二年級學生英語口說能力有正向之影響。根據以上研究結果，提出具體建議，以供相關教學實施或後續研究之參考。 The aim of this study was to address the influence of implementing English-only instruction to promote the English speaking proficiency of rural junior high school students. This study employed both quantitative and qualitative approaches by way of action research to collect and analyze the data. Twenty-three eighth grade students of Le-Le High School in Pingtung County were invited to participate in the present study. They participated in the English-only instructions for ten weeks with two periods of class per week. The ten-week English-only activities were mainly designed according to the content of the English textbook, published by Kang Hsuan Educational Publishing Group, as well as Let's Talk in English magazine published in September, 2018. The English speaking proficiency of the students was examined through a test designed by the foreign instructor and the researcher. Furthermore, the class observation logs, interviews, and students' learning feedback were adopted to analyze the implementation of English-only instruction to promote junior high school students' English speaking proficiency. Results indicated that in order to achieve the teaching goals, it was better to implement English-only instruction to go with the English-only teaching plan which meets students' needs. Moreover, the English-only instruction required a lot of communicative activities to promote students' English speaking proficiency while implementing English-only instruction. Additionally, the design of differentiated instruction was needed to achieve the instruction goals while implementing English-only instruction. As a result, the students' English speaking proficiency was enhanced by way of English-only instruction. Based on the conclusions, this study offered specific recommendations for future implementations of studies of English-only instruction.